Novel Antitumor Acetamide, Pyrrole, Pyrrolopyrimidine, Thiocyanate, Hydrazone, Pyrazole, Isothiocyanate and Thiophene Derivatives Containing a Biologically Active Pyrazole Moiety - Alqasoumi, Saleh I.; Ghorab, Moustafa M.; Ismail, Zeinab H.; Abdel-Gawad, Soad M.; El-Gaby, Mohamed S.A.; Aly, Hala M. (Arzneimittelforschung, 2009)
4-Amino-N-(1-phenyl-1H-pyrazol-5-yl)-benzenesulfonamide (sulfaphenazole) 1 was selected as strategic starting material for the synthesis of some novel acetamide 2, pyrrole 4, pyrrolo[2,3-d]pyrimidine 5, thiocyanate 6, hydrazone 7a,b pyrazole 8, isothiocyanate 9 and thiophene 12 derivatives to evaluate the antitumor activity. Compound 4 was more effective than the reference drug, doxorubicin (CAS 23214-92-8) as positive control.
Keywords: Acetamide, hydrazone, pyrazole derivatives, pyrrole, pyrrolopyrimidine, thiocyanate; Antitumor activity